2019
DOI: 10.4103/ajm.ajm_8_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasitic infections among university female students, Gaza, Palestine

Abstract: Background:The intestinal parasites are still endemic among children, women, and men in Gaza Strip.Objectives:To the best of our knowledge, this is the first study of intestinal parasites among young female students of Islamic University of Gaza to report the existence and prevalence of intestinal parasites.Methods:A total of 305 stool samples were collected from female students in all faculties and were examined by wet mount and formal ether sedimentation technique.Results:This study showed that the overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
4
3
0
Order By: Relevance
“…The present study is consistent with previous studies from Dhaka University in Bangladesh 23.14% and university female students of Gaza in Palestine 20.6% [17,18]. The existence of such similarity probably might be comparable sample size and study populations were included in all studies.…”
Section: Prevalence Of Intestinal Parasitesupporting
confidence: 92%
See 1 more Smart Citation
“…The present study is consistent with previous studies from Dhaka University in Bangladesh 23.14% and university female students of Gaza in Palestine 20.6% [17,18]. The existence of such similarity probably might be comparable sample size and study populations were included in all studies.…”
Section: Prevalence Of Intestinal Parasitesupporting
confidence: 92%
“…In this study Entamoeba histolytica/dispar was the most predominant parasite (13.0%) followed by G. lamblia (5.6%).Similar finding were reported from Dhaka university in Bangladesh as Entamoeba histolytica (4.86 %,) were the predominant parasite isolated followed by Giardia intestinalis [17]. Moreover a study from Gaza in also revealed among detected intestinal parasites: Entamoeba histolytica/dispar were (7.5%) followed Giardia lamblia (4.9%) [18].…”
Section: Prevalence Of Intestinal Parasitesupporting
confidence: 86%
“…The present study is consistent with previous studies from Dhaka university in Bangladesh 23.14% (17) and university female students of Gaza in Palestine 20.6% (18). The existence of such similarity probably might be comparable sample size and study populations were included in all studies.…”
Section: Factors Associated Intestinal Parasite Infectionsupporting
confidence: 92%
“…In this study Entamoeba histolytica/dispar was the most predominant parasite (13.0%) followed by G. lamblia (5.6%).Similar nding were reported from dhaka university in Bangladesh as Entamoeba histolytica(4.86%,) were the predominant parasite isolated followed by Giardia intestinalis (17). Moreover a study from Gaza in also revealed among detected intestinal parasites: Entamoeba histolytica/dispar were (7.5%) followed Giardia lamblia (4.9%) (18).…”
Section: Factors Associated Intestinal Parasite Infectionsupporting
confidence: 85%
“…The high prevalence of parasites infection in children is attributed to many factors, particularly environmental and personal hygiene (5). Despite the improvement of infrastructure of Gaza Strip the existence of intestinal parasitic diseases (IPD) in Gaza strip is still constituting a health problem and was approved by many studies and the general prevalence was ranged between 20-40% (6)(7). Many studies about IPD have been carried out among school-age and preschool children either in Gaza Strip (8).…”
Section: Open Access Jpurnalmentioning
confidence: 99%